Strategic Interest and Media: A Global Perspective - Nyiam, Davina (Program Studi Sosiologi, 2020)
Media has also been used as psychological warfare and a propaganda tool, particularly during times of wars and acts of insurgency. It has been used as a tool while fighting the wars and boosting the morale of the security forces across the nations. Propaganda, although it has existed almost indefinitely, has grown immensely during the past few centuries as a most strategic tool to guard the strategic interests of the nations. The propaganda was bolstered by the invention of the radio. The ability to communicate orally with a large number of people in a very small amount of time also helped the development of propaganda. This form of mass media has been used as the most effective tool with the government agencies to put forth their news and views. Radio has strategically suited governments across the globe to fight psychological wars by airing propaganda into the territories of the neighbouring countries. Since Radio is affordable and speaks in a local language and customs to a very common man, it has definitely an edge over other formats of communication when it comes to the question of guarding the strategic interests of a nation. This research discusses and deals with the strategic interests and the media and how radio has especially been used worldwide as a tool by a number of countries to safeguard their national interests. This chapter touches upon some theories and elements of propaganda, the use of radio during world wars and how countries guarded their strategic interests in the Cold War and Post-Cold War era.